2010
DOI: 10.1080/17470210903474286
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing and alleviating the impact of performance pressure on mathematical problem solving

Abstract: High-pressure academic testing situations can lead people to perform below their actual ability levels by co-opting working memory (WM) resources needed for the task at hand (Beilock, 2008). In the current work we examine how performance pressure impacts WM and design an intervention to alleviate pressure's negative impact. Specifically, we explore the hypothesis that high-pressure situations trigger distracting thoughts and worries that rely heavily on verbal WM. Individuals performed verbally based and spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 27 publications
(34 reference statements)
4
51
0
Order By: Relevance
“…The studies reviewed appear to verify the effects of self-talk on performance when the evaluation is preceded by the use of instructional self-talk compared with when self-talk is suppressed (DeCaro et al, 2010), or by the use of positive compared to negative self-talk (Cumming, Nordin, Horton, & Reynolds, 2006). In these works, and in many others, self-talk is contingent upon performance of the task.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies reviewed appear to verify the effects of self-talk on performance when the evaluation is preceded by the use of instructional self-talk compared with when self-talk is suppressed (DeCaro et al, 2010), or by the use of positive compared to negative self-talk (Cumming, Nordin, Horton, & Reynolds, 2006). In these works, and in many others, self-talk is contingent upon performance of the task.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have consistently supported a role for the use of positive self-talk compared to no self-talk (DeCaro et al 2010;Emerson & Miyake, 2003). In fact, the suppression of self-talk, by making students perform another simple verbal task at the same time as the main task, can affect self-control, leading to a more impulsive behaviour (Tullett & Inzlicht, 2010) and decreasing performance in the task (Emerson & Miyake, 2003;Goschke, 2000;Miyake, Emerson, Padilla, & Ahn, 2004).…”
Section: Self-talk and Academic Performancementioning
confidence: 99%
See 2 more Smart Citations
“…A related body of research has demonstrated that high-pressure testing situations generally increased worrying and negative thinking in participants, which reduced performance on WM-demanding math problems (DeCaro, Rotar, Kendra, & Beilock, 2010). Other research has demonstrated that even mild symptoms of anxiety on visual and auditory tasks can lead to poor working memory performance, poor concentration on said tasks, and possibly poor academic performance (Aronen, Vuontela, Steenari, Salmi, & Carlson, 2005).…”
Section: Cognitive Test Anxiety and Academic Performancementioning
confidence: 99%